The environmental impact of container pipeline transport compared to road transport. Case study in the Antwerp Harbor region and some general extrapolations. - Braet, Johan
Purpose Increasing mobility demands and growing industrial tissue come with a burden for the environment. Inventive solutions are necessary to address this challenge. This paper compares the environmental impact of two alternative container transportation methods over a 25 year time period for a specific trajectory and transport volume in the Antwerp harbor. One is a pipeline concept; the other a road concept to link the Duerganck dock with the right bank in order to transport 2 million containers per year. Materials and methods With a detailed bill of material and the use of the Ecolizer method, a Monte Carlo simulation was performed to calculate the environmental impact in terms of ECOPOINTS on a life cycle perspective. Results and discussion The results remark that in 94 percent of the cases the pipeline concept has less than half of the environmental impact of the road concept. Furthermore, in both concepts the operational phase is the largest contributor to the total environment impact. Conclusions The pipeline concept results suggest a much lower total environmental impact over a road concept if a large enough volume of containers can effectively be transported. Some considerations have to be given to the used electricity mix, the applied impact assessment method and the case specificities.
Keywords: Antwerp Harbor; Ecolizer; Environmental impact; Life cycle assessment; Pipeline transport; Road transport